2020
DOI: 10.1093/jxb/eraa424
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing secondary metabolites that shape the composition and function of the plant microbiome

Abstract: One of the major questions in contemporary plant science involves determining the functional mechanisms that plants use to shape their microbiome. Plants produce a plethora of chemically diverse secondary metabolites, many of which exert bioactive functions on microorganisms. Several recent publications have unequivocally shown that plant secondary metabolites affect microbiome composition and function. These studies have pinpointed that the microbiome can be influenced by a diverse set of molecules, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 110 publications
2
106
0
4
Order By: Relevance
“…Recent studies have shown, however, that some plant specialized metabolites contribute to plant species-specific community profiles in the rhizosphere. For example, salicylic acid, camalexin, coumarins, and glucosinolates play an important role in shaping the Arabidopsis thaliana rhizosphere (Harbort et al, 2020;Jacoby et al, 2020;Koprivova et al, 2019;Lebeis et al, 2015;Stringlis et al, 2018;Voges et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown, however, that some plant specialized metabolites contribute to plant species-specific community profiles in the rhizosphere. For example, salicylic acid, camalexin, coumarins, and glucosinolates play an important role in shaping the Arabidopsis thaliana rhizosphere (Harbort et al, 2020;Jacoby et al, 2020;Koprivova et al, 2019;Lebeis et al, 2015;Stringlis et al, 2018;Voges et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[197]. The Agrobacterium-induced microbial community shift exerted beneficial effects to bean plants by increasing overall plant biomass, antioxidants, flavonoids, potassium content, and root nodules [197,198]. Moreover, co-inoculating the rhizospheres of tomato with Stenotrophomonas maltophilia and Pseudomonas stutzeri boosted the plant growth and stimulated the production of diffusible compounds (i.e., dimethyl disulphide), which are active against the foliar pathogen Botrytis cinerea [199].…”
Section: Microbiome Engineering Using Artificial Microbial Consortiamentioning
confidence: 99%
“…For practical applications, the aim must be to identify microbial consortia affecting specific plant traits (Vílchez et al, 2016;Oyserman et al, 2018), then strong and weak phenotypic responders among plant varieties could be identified by bulk segregant analysis, and resulting inbred lines after crossing a strong and weak responder cultivar can be used to identify plant molecular control points through quantitative trait loci (Quarrie et al, 1999;Phillips and Strong, 2003). Current plant microbiome studies are often still rather descriptive, but the tools are available to approach hypothesesdriven, targeted manipulations of plant microbiomes to improve plant breeding for a more sustainable agriculture (Wei and Jousset, 2017;Jacoby et al, 2021).…”
Section: Outlook and Applicationmentioning
confidence: 99%